Model Pemilihan Moda Angkutan Laut Dan Penyeberangan Suatu Aplikasi Stated Preference Untuk Studi Kasus Rute Kendari - Raha Di Sultra - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Biologi UGM, 2000)
The aim of the paper is to demonstrate the users response of the inter insular water transport that can he quantified with the probability of mode choice based on the travel cost. frequency. travel time, service condition. and other factors. The characteristics of income level, education level and age which are different on each mode will create different responses on the change of transport cost, travel time, frequency and service. Those can he seen in the changes of elasticity values. If the component of cost increase by 1%, demand will decrease by 0.58% for wood ship. 0.02% for express boat and 0.20% for ferry services. If the travel time was increased by 1%, the demand will decrease 0.31% for wood ship, 0.16% for express boat and 0.26% for ferry. The elasticity of frequency change 1% causes an increase of demand 0.07%. for wood ship, 0.08% for express boat, and 0.07% for terry services. The elasticity of service was increased I% will cause an increase of the demand of 0.14% for wood ship. 0.11% for express boat, and 0.18%. for terry.